Clinical and hematological analysis of testicular torsion in children - Deng, Qi-Fei; Yang, Chao; Mao, Changkun; Chu, Han (Frontiers in Pediatrics, 2024)
Purpose ： Analyze the clinical manifestations, laboratory tests, and imaging data of testicular torsion to provide clinical insights for timely and accurate diagnosis and treatment of testicular torsion. Methods：A retrospective analysis was conducted on the clinical data of 67 pediatric patients suspected of testicular torsion, admitted and subjected to surgical exploration from June 2018 to June 2023. Based on whether the torsed testicle was excised during surgery, the patients were divided into orchiectomy group (40 cases) and orchidopexy group (27 cases). Combining clinical symptoms, signs, ultrasound examinations, and laboratory tests, the study aimed to summarize the influencing factors on the onset, diagnosis, and treatment of testicular torsion. Results: The clinical manifestations of all 67 pediatric patients were generally typical. Color Doppler Flow Imaging (CDFI) and surgical explorationwere performed for all cases, and the results were consistent. Testicular color doppler ultrasound suggested reduced or absent blood flow, leading to surgical treatment in all cases. All patients had unilateral testicular torsion, with 46 cases (68.66%) on the left side and 21 cases (31.34%) on the right side. Intrafunicular torsion occurred in 60 cases (89.55%), while extrafunicular torsion occurred in 7 cases (10.45%). The onset distribution was as follows: 20 cases in spring, 16 cases in summer, 16 cases in autumn, and 15 cases in winter. Univariate analysis indicated significant statistical differences in age, degree of testicular torsion, duration of symptoms, NEUT, NLR, and occurrence of tunica fluid between the two groups of patients. Multivariate logistic regression analysis showed that the duration of symptoms and the occurrence of hydrocele were independent risk factors for determining testicular viability.Testicular torsion is more common in children and adolescents, with clinical manifestations including scrotal pain, scrotal redness and swelling, abdominal pain, nausea, and vomiting. In the early stages of testicular torsion, inflammatory markers in the blood increase, and preoperative ultrasound indicates hydrocele. This suggests that the testicle is in an early twisted state, with good viability and potential for preservation.